2003
DOI: 10.1046/j.1365-313x.2003.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a pine MYB that regulates lignification

Abstract: SummaryA member of the R2R3-MYB family of transcription factors was cloned from a cDNA library constructed from RNA isolated from differentiating pine xylem. This MYB, Pinus taeda MYB4 (PtMYB4), is expressed in cells undergoing ligni®cation, as revealed by in situ RT-PCR. Electrophoretic mobility shift assays (EMSAs) showed that recombinant PtMYB4 protein is able to bind to DNA motifs known as AC elements. AC elements are ubiquitous in the promoters of genes encoding lignin biosynthetic enzymes. Transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
268
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(280 citation statements)
references
References 72 publications
7
268
0
Order By: Relevance
“…1 have been identified, and many of the enzymatic steps have been down-regulated in transgenic plants. The results of these studies (24)(25)(26)(27)(28)(29)(30) have generally confirmed the pathway in Fig. 1 and supported increasing S͞G ratio as a means of improving paper pulping in trees.…”
supporting
confidence: 72%
“…1 have been identified, and many of the enzymatic steps have been down-regulated in transgenic plants. The results of these studies (24)(25)(26)(27)(28)(29)(30) have generally confirmed the pathway in Fig. 1 and supported increasing S͞G ratio as a means of improving paper pulping in trees.…”
supporting
confidence: 72%
“…Several genes encoding enzymes in the general phenylpropanoid pathway and in the synthesis of lignin precursors contain common motifs that are recognized by specific transcription factors, such as MYBs (Borevitz et al, 2000;Patzlaff et al, 2003). The QTLs we identified here could represent such transcription factors.…”
Section: Discussionmentioning
confidence: 82%
“…Indole-3-acetic acid has been shown to function as a positional signal for xylem differentiation (Uggla et al, 1998;Mellerowicz et al, 2001). Specific transcription factors, such as members of the R2R3-MYB gene family, are also likely to control lignification during xylogenesis (Patzlaff et al, 2003). Despite the progress in defining the molecular and cellular processes involved, the mechanisms that determine the rate of xylogenesis (wood growth) and variation in wood properties remain largely unknown.…”
mentioning
confidence: 99%
“…Similar results were also reported for loblolly pine MYB1 and MYB4 (Patzlaff et al ., 2003a,b). PgNAC‐7 and these three MYBs were proposed by Duval et al .…”
Section: Discussionmentioning
confidence: 99%
“…The other genes that were connected to PgMYB8 , PgMYB4 and PgNAC‐7 , suggesting that their regulation depends on several transcription factors. These results support observations that several different MYBs may act in concert to regulate different portions of phenylpropanoid metabolism and lignin biosynthesis at different times in conifer trees (Patzlaff et al ., 2003a; Bomal et al ., 2014). …”
Section: Discussionmentioning
confidence: 99%